This is not a C#: What My Computer Means. (Organised Sound, 2008)
AbstractComputers contain layers of abstraction between the raw audio bits and the user experience; each layer requires a method of traversal that reflects the attitudes of the programmer/composer/performer. The navigation of this hierarchy results in modes of thought that affect notions of how musical signifiers can be subverted and redefined. This explosion of individualistic technological systems defines meaning for new sonic results, devoid of traditional communicative signs; the manipulations within these systems directly assail the traditional signification of artistic value and of institutional canonisation. A few pieces and scenarios are presented as examples. Additionally presented are two opposing tendencies (with some empirical manifestations) in the creation of live performances systems, here labelled as extensional and algorithmic. The article posits that a performance system cannot amplify human expression without necessarily having either predefined processes or predefined limitations, and that the choice in this design is reflected in the composer's attitude towards layer-traversal.